An Ethical Survey on Non-Delay Tolerant Routing Protocols for VANET - Devi, S. Suguna; Bhuvaneswari, A (International Journal of Computer Sciences and Engineering, 2025)
Intelligent Transportation system is a potential system which uses Vehicular Ad hoc Networks (VANET) with internet for its safety driven applications. VANET is infrastructure less and the vehicles form a self-structured network. During data forwarding, the vehicles undergo congestion which is a vital issue related to VANET. To overcome this the data has to be propagated in a particular path in optimized fashion . Routing protocols play a vital role for the propagation of data among nodes. This paper reveals the general idea of position routing protocols with much emphasize on Non delay routing protocols. Various parameters such as packet delivery ratio , end to end delay , throughput and cost were analyzed using hybrid NDTN routing protocols. It also focuses on various aspects of VANET like architecture, an overview of routing protocols, position based routing protocols, classification and related works contributed by various researchers